The Influence of Financial Behavior, Attitude, Knowledge and Skills on Financial Inclusion of People of Batam City - Fendy Cuandra; Anjela Anjela (Universitas Bunda Mulia, 2021)
Financial Inclusion is the use or access of the individual to financial products and services. The purpose of this study was to examine the effect of financial literacy components consisting of financial skills, knowledge, behavior and attitude towards community financial inclusion in Batam City, Indonesia. The data were obtained from randomly distributing questionnaires to 400 samples of the people of Batam City. The research data were processed using SmartPLS 3.0 software. Based on the data analysis, the research conducted shows that all components of financial literacy, namely financial skills, knowledge, behavior and attitude have a significant effect on the financial inclusion of the people of Batam City. In addition, the results of this study also show that there is a significant influence on financial knowledge, behavior and attitude on financial literacy.